3D model of harlequin ichthyosis reveals inflammatory therapeutic targets - Enjalbert, Florence (J Clin Invest, 2020)
The biology of harlequin ichthyosis (HI), a devastating skin disorder caused by loss-of-function mutations in the gene ABCA12, is poorly understood, and to date, no satisfactory treatment has been developed. We sought to investigate pathomechanisms of HI that could lead to the identification of new treatments for improving patients’ quality of life. In this study, RNA-Seq and functional assays were performed to define the effects of loss of ABCA12 using HI patient skin samples and an engineered CRISPR/Cas9 ABCA12 KO cell line. The HI living skin equivalent (3D model) recapitulated the HI skin phenotype. The cytokines IL-36α and IL-36γ were upregulated in HI skin, whereas the innate immune inhibitor IL-37 was strongly downregulated. We also identified STAT1 and its downstream target inducible nitric oxide synthase (NOS2) as being upregulated in the in vitro HI 3D model and HI patient skin samples. Inhibition of NOS2 using the inhibitor 1400W or the JAK inhibitor tofacitinib dramatically improved the in vitro HI phenotype by restoring the lipid barrier in the HI 3D model. Our study has identified dysregulated pathways in HI skin that are feasible therapeutic targets.